Wireless Sensor Network for Monitoring Rice Crop Growth - ajibekti, ari; Munadi, Rendy; Rahmat, Basuki (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2018)
For observation of rice plants continuously against climatic influences of rice plants in the vegetative stage,reproductive stage, ripening stage by measuring the pH level, temperature, soil moisture using the technology of WirelessSensor Network (WSN). The purpose of this study to monitor climate effects on the growth of rice plants with the technologyWireless sensor network (WSN). The design and implementation of WSN based on Zigbee platform and Arduino withobservation method involve monitoring the change of indicator of each sensor node, distance parameter, delay parameter oneach rice growth. Testing the performance of WSN through parameter RSSI (receive signal strength indicator) between the enddevice and the coordinator through software applications XCTU do at every stage of rice growth. Test results at a distance of100 meters obtained the average value of RSSI in the vegetative stage of -80.40 dBm, at the reproductive stage of -83.72 dBm,and at the ripening stage of -84.44 dBm. The WSN implementation, testing using cluster tree topology is done at a different time.The test is performed between the sensor node to the node coordinator in the topology of the cluster tree in different areas. Theresult of the measurement of data delivery delay is 312ms for the area of 1 hectare of rice field at 120 days of age with the nodenumber of 7 units. Furthermore, with the node number 7 units, 376ms for the paddy field with 2 hectare area. The results ofWSN implementation experiments on 2 hectares of rice farming area can provide real time information so as to contribute inagriculture when there is a change of climatic conditions or sudden pest diseases that affect the results of rice crop productivityand food security.